Kinetic modeling of cement slurry synthesized with Henna extract in oil well acidizing treatments - Amir Hossein Aghajafari; Seyed Reza Shadizadeh; Khalil Shahbazi; Hadi Tabandehjou (Petroleum, 2016)
Acidizing treatment in petroleum reservoirs is a short-term and viable strategy to preserve the productivity of a well. There is a major concern for the degradation of cement sheath integrity, leading to poor zonal isolation and environmental issues. Therefore, it is essential to understand how the cement behaves when attacked by hydrochloric acid. In this study, a cement slurry by incorporation of the Henna extract, as an environmentally friendly cement additive, was synthesized as a potential solution to solve this problem. The characteristics of the treated cement slurry were compared with a reference slurry (w/c = 0.44) which is composed of only cement and water. A kinetic study was carried out to evaluate the adsorption behavior of the cement slurries exposed to an acid solution with 0.1 M HCl in a range of 25 to 55 °C conditions. The features of the cement slurries were evaluated by multiple analytical techniques such as XRD, FTIR, TG, and DSC analysis. From the experimental data, it is concluded that the second-order Lagergren kinetic model revealed to be the best in describing kinetic isotherms taken, because the margin between experimental and calculated values was minor for this model. The results of the characterization and HCl interaction kinetic studies underlined the prominent protective role of Henna extract-modified cement slurry in the enhancement of the cement resistance against acid attack and utilization in environmentally favorable oil well acidizing treatments.